2011
DOI: 10.1002/chem.201102179
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Features and Recognition Properties of a Conformationally Blocked Calix[7]arene Derivative

Abstract: The shaping of a calix[7]arene macrocycle into cone-like structure 3, through exhaustive alkylation of doubly bridged calix[7]arene derivative 2 with bulky groups, has been investigated. Conformational details about the structure adopted by calix[7]arene derivative 3 in solution have been obtained by using chemical shift surface maps, as previously reported by our group. Thus, chemical shift contour plots indicated that 3 adopted a cone-shaped structure in solution analogous to that adopted by the known p-tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…In fact, the hexamer started to appear after 10 min and remains the favored product over time, whereas the equilibrium value of 75 % was reached after 45 min. HPLC analysis (SI) revealed that the pentamer appeared after 15 min but vanished immediately after 30 (30 -45 min). Similar results were observed for the reaction in Scheme 1 starting from propoxy precursor 4c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the hexamer started to appear after 10 min and remains the favored product over time, whereas the equilibrium value of 75 % was reached after 45 min. HPLC analysis (SI) revealed that the pentamer appeared after 15 min but vanished immediately after 30 (30 -45 min). Similar results were observed for the reaction in Scheme 1 starting from propoxy precursor 4c.…”
Section: Resultsmentioning
confidence: 99%
“…The complexation of N,N,N',N'-tetramethylpiperazonium 7 2+ cation (Scheme 2) showed very interesting features. Addition of 1 equiv of 7 2+ as barfate salt (BArF -) 30,31 to a solution of PrS[6] nPr in CD 2 Cl 2 caused significant changes in its 1 H NMR spectrum (Figure 6), indicative of the formation of 7 2+ @PrS[6] nPr complex with the cation hosted inside the cavity of PrS[6] nPr . Furthermore, in the presence of 7 2+ , a more symmetric conformation of PrS[6] nPr emerged in the 1D and 2D NMR spectra (SI).…”
Section: Molecular Recognition Properties Of Ethoxy-and Propoxyprism[n]mentioning
confidence: 99%
“…Hydrophobic TFPB – , which is known to be a weakly coordinating anion,[32a] was chosen as the counteranion because of the good solubility of its sodium salt in organic solvents. [32b] As previously shown by us,[3a], [4b], [4c] the good solubility of TFPB – salts in CDCl 3 enable the determination of the apparent association constant of the complex by direct integration of its 1 H NMR spectroscopic signals with respect to those of the free host.…”
Section: Resultsmentioning
confidence: 88%
“…Calix[ n ]arenes are a well‐known class of macrocyclic compounds that have been widely exploited in the last decades as a result of their particular three‐dimensional shape and ease of functionalization The synthetic versatility of calixarene macrocycles makes them suitable for a wide range of applications that include molecular recognition and sensing, synthesis of interpenetrated architectures, biomolecular recognition, and catalysis . It has long been known that calix[4]arene‐amide hosts show a high affinity towards alkali metal cations , .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the possible types of wheels, more recently, we have introduced the through-the-annulus threading of simple calix[6]arene hosts with dialkylammonium axles [1726] by exploiting the inducing effect of the superweak tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (TFPB) anion that gives free ‘naked’ dialkylammonium cations. In addition, we have reported interesting examples of endo -cavity complexation of alkylammonium cations, as TFPB − salts, inside the aromatic cavity of calixarene [20] and dihomooxacalixarene hosts [2122]. Thus, through this ‘superweak anion’ approach, we have synthesized interesting examples of calixarene/ammonium-based interlocked structures such as calix-rotaxanes [2324] and calix-catenanes [25].…”
Section: Introductionmentioning
confidence: 99%